2015
DOI: 10.1152/ajpheart.00072.2015
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial ATP hydrolysis rates in vivo: a porcine model of pressure overload-induced hypertrophy

Abstract: Myocardial ATP hydrolysis rates in vivo: a porcine model of pressure overload-induced hypertrophy. Am J Physiol Heart Circ Physiol 309: H450 -H458, 2015. First published May 29, 2015 doi:10.1152/ajpheart.00072.2015 hypertrophy (LVH) and congestive heart failure are accompanied by changes in myocardial ATP metabolism. However, the rate of ATP hydrolysis cannot be measured in the in vivo heart with the conventional techniques. Here, we used a double-saturation phosphorous-31 magnetic resonance spectroscopy-magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…In either case, the observed decrease in ATPase activity may help to preserve [ATP] in the face of a decrease in synthesis, albeit, at the expense of a decrease in myocyte work performed [39]. Importantly, our findings are consistent with previously published in vivo studies from normal [44] and hypertrophied hearts [45,46]. …”
Section: Discussionsupporting
confidence: 90%
“…In either case, the observed decrease in ATPase activity may help to preserve [ATP] in the face of a decrease in synthesis, albeit, at the expense of a decrease in myocyte work performed [39]. Importantly, our findings are consistent with previously published in vivo studies from normal [44] and hypertrophied hearts [45,46]. …”
Section: Discussionsupporting
confidence: 90%
“…Although its chemical shifts depend on blood oxygenation, red blood cell 2,3‐DPG has been reported to be 100% visible in vitro by 31 P NMR. Observation of blood 2,3‐DPG 31 P signals have been reported in the PME and P i region (5–7 ppm) in several cardiac 31 P studies in vivo . In some cases, the 2,3‐DPG signals can be resolved into 2 separate peaks .…”
Section: Discussionmentioning
confidence: 91%
“…In addition to the progressive LVPO model, and our previously described sheep model of acute aortic constriction, which induced rapid deterioration to HF/death, others have also employed aortic constriction in pigs. Acute onset aortic constriction beyond the carotid bifurcation resulted in rapid induction of LVH with reduced LVEF and acute HF by Day 7 (including death in 4/22 pigs), which then over 7 weeks evolved into a compensated phase of concentric LVH with restored cardiac function . Thus, there is need to induce LVPO in a progressive nature as implemented in this study to induce progressive LVH without systolic dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…Acute onset aortic constriction beyond the carotid bifurcation resulted in rapid induction of LVH with reduced LVEF and acute HF by Day 7 (including death in 4/22 pigs), which then over 7 weeks evolved into a compensated phase of concentric LVH with restored cardiac function. 25 Thus, there is need to induce LVPO in a progressive nature as implemented in this study to induce progressive LVH without systolic dysfunction. Other authors banded ascending aorta of minipigs (25-30 kg) but showed no significant LVH or change in left atrial volume or LVEDP over 20 weeks and did not report of plasma BNP.…”
Section: Discussionmentioning
confidence: 99%